2015
DOI: 10.1021/je500786e
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Castor Oil-Based Ionic Liquid Microemulsions: Effects of Ionic Liquids, Surfactants, and Cosurfactants

Abstract: Castor oil-based ionic liquid microemulsions are promising alternatives for petroleum-based biolubricant basestocks. This study presents the phase behavior of castor oil-based ionic liquid microemulsions through phase manifestation, and the areas of the single-phase domain (S ME ) were calculated accordingly to further illustrate the phase-forming capacities of the designed microemulsions. The results indicated that the phase-forming capacities of castor oil-based ionic liquid microemulsions depended largely o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Therefore, the results proved that EtOH could exist as a cosolvent in the [Emim]­[Tf 2 N]/CO 2 microemulsion system. The addition of EtOH reduced the radius of the spontaneous curvature, so the construction of the microemulsion became easier …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the results proved that EtOH could exist as a cosolvent in the [Emim]­[Tf 2 N]/CO 2 microemulsion system. The addition of EtOH reduced the radius of the spontaneous curvature, so the construction of the microemulsion became easier …”
Section: Results and Discussionmentioning
confidence: 99%
“…The addition of EtOH reduced the radius of the spontaneous curvature, so the construction of the microemulsion became easier. 55 For the Ls-45 system, it was found that the higher the temperature, the smaller the effect of EtOH concentration on the CPP. For example, at 35 °C, when the concentration of [Emim][Tf 2 N] was 1.0 mmol/L, the gap in CPP between W E = 1.5 and 3 was about 0.5 MPa.…”
Section: Simulation Detailsmentioning
confidence: 99%